POTENSI BATUGAMPING TERUMBU GORONTALO SEBAGAI BAHAN GALIAN INDUSTRI BERDASARKAN ANALISIS GEOKIMIA XRF - Rini Rahmatia S; Aang Panji Permana; Ronal Hutagalung (EnviroScienteae, 2023)
Reservoir rocks are hollow rocks below the surface that are capable of storing and flowing groundwater that can be utilized by the community. The limestone facies is a good reservoir rock. The characteristics of the limestone facies in the Ombulo Region, Gorontalo Regency, which reach 3.42 km2, are very interesting to study. This study aims to analyze the porosity value of each limestone facies in the study area. The research method used consisted of field geological surveys and petrographic laboratory analysis. The results showed that the study area consisted of four limestone facies namely floatstone facies, mudstone facies, wackestone facies, and rudstone facies. The potential of limestone in the Ombulo area as reservoir rock is in the poor to very good category.